KAJIAN FRAKTAL i-FIBONACCI WORD GENERALISASI GANJIL DENGAN MENGGUNAKAN L-SYSTEM - Umami, Riza; Purnomo, Kosala Dwija; Ubaidillah, Firdaus (Majalah Ilmiah Matematika dan Statistika, 2019)
The i-Fibonacci Words are words over {0,1}. The i-Fibonacci Word can be associated with a fractal curve by using odd-even drawing rule and L-System methods, then also known as an i-Fibonacci Word fractal. L-System is one of methods that is used to create objects with repetitive self-similiarity. Framework of L-System consists of axiom and rules. L-System is a parallel rewriting system with existing rules. The purpose of this research is to look for the LSystem rules of i-Fibonacci Word special for odd i, then look how its characteristics. The LSystem rules for i-Fibonacci Word odd i are divided into two types, the rules for i=1 and the others odd i. The characteristic of i-Fibonacci Word fractal is the more generation and i value of fractal, then the more segments and archs of fractal curve. Next, the words of i-Fibonacci Word fractal segments number is a subwords of the i-Fibonacci Word digit numbers. It is also known that the fractal curve will be stretched as the decreased angle. Keywords: Fractal, i-Fibonacci Word, L-System